Introduction to crop wild relatives - Volk, Gayle M.; Khoury, Colin K.; Greene, Stephanie L.; Byrne, Patrick (Colorado State University Press, 2020)
Food production has advanced from the original form where humans gathered food from the wild, to cultivation and selection of wild plants (landraces), and further to modern-day plant breeding of new varieties and cultivars with high quality, yields, and resistance to abiotic and biotic stresses. Food crops have been derived from wild plant species (crop wild relatives) from throughout the world and are now cultivated in locations that may be far from their original sources. Here, we provide information and illustrations about where food crops originated and we highlight the important work of the Russian Geneticist Dr. Nikolai Vavilov, who introduced the concept of “centre of origin” for crop plants and encouraged the conservation and use of crop wild relatives for plant improvement.